(untitled) (Szociológiai Szemle, 2023)
The Hungarian pension system has experienced strikingly hectic changes over the past decades. Hungary adopted the Argentinean pension model in 1997, which included a compulsory private pension pillar. Thirteen years later, during the economic crisis, the conservative cabinet decided to fully eliminate the mandatory private pillar (the voluntary private pillar remained). This paper is written to assess the impact of the 2010-2012 reforms, with a view not only to examining the nationalization of private pension funds, but also the less discussed elements of the reform package concerning early retirement rules, the disability pension scheme, and social insurance contributions. Our main research question is whether the reforms led to a more sustainable and more equitable pension system. We provide a somewhat paradoxical answer: despite the lack of consultation with stakeholders and the extreme speed of the reform, the overall impact of changes is slightly positive as they have improved the financial sustainability of the Hungarian pension system in the short- and mid-term, while also increasing pension adequacy and replacement rates. The prospects of the pension system in the long run, however, raise serious concerns related to both sustainability and equity. One foreseeable negative process is the increasing inequality among new pensioners, and the growing share of poor among the elderly.